2024
DOI: 10.37978/tijfs.v4i2.291
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Analysis of COVID-19 Confirmed Cases in Pakistan

Abstract: Introduction: COVID-19, a novel disease, appeared in December 2019 in China and rapidly spread across the world. Till the second week of April 2020, high incidence (2.9/100,000) and cases fatality rates (1.7%) were observed in Pakistan. This study was conducted to determine the temporal and spatial distribution of the first 100 deaths attributed to COVID-19 in Pakistan and their associated demographic factors. Method: A record review of the first 100 deaths reported among RT-PCR confirmed COVID-19 cases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
6
1
Order By: Relevance
“…In contrast, our study showed an insignificant difference between both genders in terms of COVID-19 severity. This observation was different from what was reported in the other reports from EMR countries [ 25 , 34 , 35 ]. This can be explained as we here investigate the risk of severity, not mortality.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, our study showed an insignificant difference between both genders in terms of COVID-19 severity. This observation was different from what was reported in the other reports from EMR countries [ 25 , 34 , 35 ]. This can be explained as we here investigate the risk of severity, not mortality.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies proposed many pathogenic mechanisms behind the critical illness in the elderly population, including low levels of angiotensin-converting enzyme 2 (ACE2) in the elderly [ 31 ], age-dependent difficulty in removing particles from small airways [ 32 ], excessive release of inflammatory mediators in elderly “inflammaging” [ 33 ], incompetent immune response, and high frequency of comorbidities in the elderly population [ 29 ]. Recent retrospective studies from Egypt [ 25 ], Iran [ 34 ], and Pakistan [ 35 ] demonstrated that older age groups were more susceptible to severe disease and death from COVID-19. This was in line with other reports from outside of EMR countries [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both of the disorders were found signi cantly associated with mortality with odds ratio of 2.49 and 1.84 respectively. These results are consistent with previous reports on the topic as both the diabetes and hypertension have been reported as signi cant risk factors for mortality among COVID-19 patients [10][11][12][13]20,[22][23][24]. Higher risk of mortality caused of these co-morbidities may be due to an impaired immunity, high coagulation activity in diabetic patients, high in ammation [14,[23][24] and the older age of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Cardiovascular diseases are always a big risk factor of mortality and in case of COVID-19 patients, it has been reported as a serious threat enhancing the risk of death to many folds [13,[19][20][21][22]. This study also pointed out that cardiovascular disease is a a serious threat raising risk of death up to 5 folds as only less than one half of the reported COVID patients with heart disorder in current study could survived and the percentages of death were 57.1% and 16.4% respectively in patients with and without CVDs with odds ratio of 5.07.…”
Section: Discussionmentioning
confidence: 99%
“…The twin cities Rawalpindi and Islamabad in Pakistan have a combined population of around 3 million people and were a hot spot during various waves of COVID-19 [8]. A few small-scale studies have been reported from Pakistan, but there is a dire need to regularly gather, document, and analyze epidemiological data from patients with COVID-19 in Pakistan in a systematic way; this is needed in order to identify high-risk groups and determine risk factors associated with poor disease prognoses, in relation with resultant morbidity or mortality [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%